IMPLEMENTASI METODE IQRO DAN UMMI DALAM MENINGKATKAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI DINIYAH TAKMILIYAH AWALIYAH (DTA) AL-IKHLAS DESA KONDANG JAYA KECAMATAN KARAWANG TIMUR KABUPATEN KARAWANG - Sucilawati; Akil; Agus Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
An important aspect of Muslim education is Islamic religious education, which aims to instill religious values ​​and principles in everyone. The Iqro and Ummi methods are used to improve Islamic learning in various environments. The aim of this research is to show how the iqra and Ummi methods are used in learning the Koran at SDIT Nurul Islam Tengaran, with a focus on application. Qualitative research can tell researchers that the Iqro and Ummi Method is a way to improve Islamic Religious Education learning in various environments. This can motivate other teachers to try using this method in Islamic religious education. This study found that the use of the Iqro and Ummi methods in Islamic religious education in the Al-Ikhlas DTA, Kondang Jaya Village improved the quality of learning and students' understanding of the Islamic religion. Keywords: Islamic Religious Education, Method, Ummi and Iqra